(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Pharyngitis is primarily a viral infection of the respiratory tract, followed by secondary bacterial invasion due to weakening of local defenses. Influenza A and rhinoviruses are principally involved, the influenza virus having much higher pathogenicity, however, than rhinoviruses which usually cause the common cough and cold without severe damage to the respiratory mucosa. Following initial infection, the virus enters the cells only for multiplication and almost all virulent virus particles subsequently produced are shed onto the throat surface. From the throat surface, the virions infect new healthy cells, damaging the throat mucosa, and creating a favorable ground for secondary bacterial colonization which is the cause of almost all symptoms of throat infection (sore throat, strep throat). The virus’ complex structure, its constant mutation, the variety of its surface glycoproteins, as well as the role of topical proteases helping virus entry and virus – bacteria symbiosis must all be taken into account in designing an effective treatment, acting on multiple parameters. As most viruses and all bacteria are present on the throat’s outer lining, treatment should be designed to act topically on the surface of the pharynx, which also minimizes side effects. Until 2012, no topical antiviral drugs were available and almost all treatment strategies were directed to relieve only the symptomatic manifestations of throat infections. Anti-influenza vaccination is still considered the best preventive measure, while the use of intracellular virus inhibitors is strictly limited to severe cases as they were not found to be very effective once throat infection is established. The recent development of non-specific topical virus glycoprotein inhibitors, incorporated in a filmogen glycerol solution for an increased duration of action, represents a breakthrough yet relatively simple scientific approach for the treatment of viral throat infections accompanied by secondary bacterial infection. In this review, we analyze the whole process of viral throat infection, virus – bacteria interactions on the throat surface, currently available treatments and their drawbacks, and this innovative therapeutic approach consisting in virus glycoprotein inhibitors in an osmotic solution, destined to totally change the future treatment of throat infections.